Sucrose hydrolysis by invertase using a membrane reactor: effect of membrane cut-off on enzyme performance - Francesco Di Addezio; Ester Junko Yoriyaz; Maria Cantarella; Michele Vitolo (Universidade de São Paulo, 2014)
Sucrose hydrolysis by invertase [EC.3.2.1.26] produces inverted sugar syrup, an ingredient mainly used in the food industry. To properly catalyze hydrolysis, the enzyme should be reused after this reaction. It is advisable to maintain constant activity over a considerable period. Thus, sucrose hydrolysis was performed in a membrane bioreactor - a continuously stirred tank reactor coupled with an ultrafiltration membrane (UFM) which provides good diffusion and high activity per unit volume. Molecular weight cut-off for soluble invertase UFMs was up to 100kDa. This study focused on the role of UFM invertase cut-off as it is the main element in the process. We demonstrated that both the cut-off and chemical nature of the UFM affected specific invertase activity.